Reference intervals of white blood cell parameters for healthy adults in japan. (15th February 2021) - Takami, Akiyoshi; Watanabe, Shinichiro; Yamamoto, Yoshikazu; Miyachi, Hayato; Bamba, Yukiharu; Ohata, Masahiko; Mishima, Seiji; Kubota, Hiroshi; Nishiura, Akihiko; Inaba, Tohru; Enomoto, Megumi; Mitsuhashi, Takayuki; et al.
Abstract: Introduction: While white blood cell (WBC) parameters have been suggested to depend on ethnicity and gender, reference intervals in healthy Asian populations are limited. The present study established reference intervals of WBC parameters for healthy adults in Japan. Methods: A total of 750 healthy adults (447 women and 303 men; 18‐67 years old, median 40 years old) at 7 Japanese centers who participated in regular medical checkups entered this study. The WBC parameters were measured using automated hematocytometers and blood film reviews by a manual microscopic examination. Results: The reference intervals of the WBC parameters according to gender in healthy adults were determined. Age‐specific decreases in WBC counts of both gender groups and in neutrophil counts of women were noted. Favorable correlations between the hematocytometer and microscopic methods were found in neutrophils, lymphocytes, and eosinophils but not in monocytes or basophils. Conclusion: This study suggests the need to consider gender and age in the clinical use of reference intervals of WBC parameters.